Pengaruh Pemberian Urin B2 Pada Lahan Tanaman Kacang Tanah - Sintikhe Wahyu Arif Lase; Iren Forjun Telaumbanua; Novita Sari Laoli; Awal Sepkurniawan Waruwu; Elman Kasih Saputra Gulo; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the effect of B2 urine, a liquid organic fertilizer produced by fermented cow urine, on the growth and yield of peanut plants (Arachis hypogaea L.). Cow urine contains nitrogen, phosphorus, potassium, and bioactive compounds that support plant growth organically. The method used was a literature review and secondary data analysis from previous studies with various doses of B2 urine application. Parameters observed included plant height, number of pods, and dry seed weight per plant. The results showed that a dose of B2 urine of around 3,000–6,000 L/ha had a positive effect on vegetative growth, especially leaf number and plant height. In addition, the combination of biourine with other organic fertilizers significantly increased seed production. The use of B2 urine has been shown to support environmentally friendly agricultural practices and reduce dependence on chemical fertilizers.